Propuesta de un plan de manejo ambiental, enfocado al recurso hídrico para los efluentes producidos en el centro de acopio de lácteos - Asociación Agropecauria El Ordeño - La Chimba, parroqia Olmedo, Cayambe - Pichincha - Guevara Avilés, Jacqueline Alexandra (2015)
The proposal of this document is the environmental management for effluents produced in the milk recollection center Agricultural Association El Ordeño - La Chimba that is located in the Olmedo’s parish, Cayambe in the northeast of Pichincha’s province. A series of guidelines are established to provide a proper environmental management to the discharge in the process of making cheese, yogurt and milk recollection, so it improves the quality of the effluent that is discharged into La Chimba River and keep the physical - chemical, microbiological and toxicological characteristics in a natural state of balance. The main point is the value of water bodies, especially those from the top of our mountains, which at lower levels are in advanced stage of pollution. The care and protection should come on the new watersheds, which is the case of La Chimba River, seeking the best ways for water in the environmental management linked with the dairy production chain as an important part of agriculture in the Ecuador’s highland.